Analysis of public policy implementation challenges in Nigeria - Ujah, John Sule; Felicia, Uloko; Innocent, Omaufedo (2020)
The work entitled “analysis of Public Policy Implementation challenges in Nigeria” seeks to examine the challenges that have continued to hinder the successful implementation of public policies in Nigeria. A general policy problem is that of inadequate and poor data which poses planning difficulties and invariably implementation challenges of projects and programmes. Unreliable data makes it difficult to make adequate projections in terms of expected outcome, needs and equipment Failure of government to meet up with the condition of coming up with an action plan as and when due impedes effective implementation of public policies. Inadequacy of policy resources also tend to undermine the successful implementation of public policies. This study recommends that the factors that plague public policy implementation agencies must be addressed. Laudable policies formulated should not go into thin air at the implementation stage. Governmental implementing agencies must be efficient and competent so as to ensure effectiveness of policy implementations. Also, corruption is of serious concern; in this regard, the issues of proper utilization of funds and accountability must be critically observed.